U.S. parents' attitudes toward playful learning - Wright, Charlotte Anne; Pasek, Josh; Lee, Ji Young; Masters, Ally S.; Golinkoff, Roberta Michnick; Thomsen, Bo Stjerne; Hirsh-Pasek, Kathy (Frontiers in Developmental Psychology, 2023)
There has been a surge of research on the power of play to facilitate learning in recent years. Guided play, specifically, has emerged as an optimal learning approach over free play and direct instruction. However, whether parents’ perceptions of play align with the emerging research remains largely unexplored. Addressing this gap, the present study is the first to operationalize play by using the playful learning spectrum (i.e., free play, guided play, games, and direct instruction) to investigate parent perceptions of play. The study surveyed a broad, national sample of parents (N = 1,172) with at least one child aged 2 and 12 years living in the United States. The findings revealed a preference for play over direct instruction, with parents likely to favor free play as most conducive to learning. Nevertheless, regression analyses uncovered significant variations in perceptions based on demographic and attitudinal factors. While the study reveals parents’ evolving, positive attitudes towards play, they also underscore a gap between academic research, which highlights the advantages of guided play, and parents’ perceptions. Implications for parent support initiatives are discussed.